Eating Disorders Impact on Vigilance and Decision Making of a Community Sample of Treatment Naive Attention-Deficit/Hyperactivity Disorder Young Adults - Nazar, Bruno Palazzo; Trindade, Amanda Pompeu; Leslie, Monica; Malloy-Diniz, Leandro Fernandes; Sergeant, Joseph; Treasure, Janet; Mattos, Paulo (Frontiers in Psychiatry, 2018)
Although impulsivity is suggested as a possible link to explain the association of Attention - Deficit / Hyperactivity Disorder (ADHD) with an Eating Disorder (ED), there is little research on how clinical and cognitive / neuropsychological functioning might change when this comorbidity occurs. ADHD individuals are at a higher of developing ED and also obesity. Some research has described the impact of ADHD in clinical treatment-seeking samples of ED patients. Consequently, we investigated how ED impacted on clinical and cognitive variables of a community sample of treatment-naive ADHD individuals. Ninety college students arranged in three groups (ADHD+ED, ADHD only and Controls) were analysed using semi-structured interviews for ADHD (K-SADS), the Iowa Gambling Task, the Conner’s Continuous Performance Test, Digit and Visual span, as well as rating scales for anxiety (STAI), depression (BDI) and impulsivity (BIS-11) and binge eating (BES). We found that ADHD+ED individuals significantly differed from both groups, presenting with a higher body mass index; more hyperactivity-impulsivity symptoms; higher binge eating scores; more omission errors on the Continuous Performance Test; disadvantageous choices on the Iowa Gambling Task. Also, we demonstrated through a moderation/mediation analysis that a greater level of binge eating mediated the increases in body mass index on our sample. There were no significant paths to explain binge-eating severity through changes on any of the neuropsychological tests used. The presence of an ED in normal weight in a community sample of ADHD individuals is associated with higher body mass index and a worse cognitive functioning.